2011
DOI: 10.1002/cvde.201006872
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol‐Assisted CVD of Titanium Dioxide Thin Films from Methanolic Solutions of Titanium Tetraisopropoxide; Substrate and Aerosol‐Selective Deposition of Rutile or Anatase

Abstract: Titanium dioxide (TiO 2 ) thin films are synthesized using aerosol-assisted (AA)CVD of titanium (IV) isopropoxide (TTIP) in methanol. Deposition is carried out on glass, steel, and titanium substrates at 400-5508C. The films produce morphologies that are radically different to those from typical aerosol-assisted processes, and from the use of TTIP in low or atmospheric pressure (AP)CVD. The films show some substrate-dependent morphology and properties. In particular at 5508C the films on steel show needle-and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 18 publications
1
28
1
Order By: Relevance
“…have shown that by changing the solvent mix to include differing proportions of methanol and ethanol, it is possible to deposit rutile TiO 2 at temperatures as low as 500 °C (cf. APCVD where rutile only forms above 750 °C) . By being able to reduce the temperature required to form a particular crystalline phase, this can significantly lower the cost of production and reduce the energy required to synthesise such films.…”
Section: Aerosol Routes To Sustainable Manufacture Of Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…have shown that by changing the solvent mix to include differing proportions of methanol and ethanol, it is possible to deposit rutile TiO 2 at temperatures as low as 500 °C (cf. APCVD where rutile only forms above 750 °C) . By being able to reduce the temperature required to form a particular crystalline phase, this can significantly lower the cost of production and reduce the energy required to synthesise such films.…”
Section: Aerosol Routes To Sustainable Manufacture Of Materialsmentioning
confidence: 99%
“…APCVD where rutile only forms above 750 8C). [39] By being able to reduce the temperature required to form ap articular crystalline phase, this can significantly lower the cost of production and reduce the energy required to synthesise such films.…”
Section: Deposition Of Binary Metal Oxide and Dopedmetal Oxide Materialsmentioning
confidence: 99%
“…The presence of the brookite phase was also observed in the [121], [221] and [203] planes. This mixture of phases is commonly observed in the production of TiO2 derived thin films [2,8], and it is believed that the sol-gel method described herein has resulted in the production of largely amorphous TiO2 thin films which cannot be detected by XRD. For further determination of the TiO2 phase, Raman spectroscopy was used, whereby a typical spectrum is shown in Figure 6.…”
Section: Crystalline Phase Identification Of Tio2 Thin Filmsmentioning
confidence: 83%
“…Titanium dioxide has been used consistently as the photocatalyst of choice to address a variety of environmental problems, and has been shown to be particularly effective when utilised as a thin film coating, specifically in self-cleaning glass [1], antimicrobial applications [2], and for water-splitting to produce hydrogen [3]. A multitude of approaches are used to produce TiO2 thin films, including sol-gel [4] and hydrothermal routes [5], as well as vapour deposition methods, such as chemical vapour deposition (CVD) [6], physical vapour deposition (PVD) [7] and more recently, aerosol-assisted CVD [8] and electric field assisted CVD [9].…”
Section: Introductionmentioning
confidence: 99%
“…34 It has been previously shown that AACVD can be used to independently synthesize films of zinc oxide from zinc acetate, and titanium dioxide using titanium isopropoxide, both in methanol solution. [35][36] In this work, we will show that by combining both precursors in a single solution in different ratios, it is possible to form films containing all of the known structures of zinc titanate, and crucially also films containing both zinc titanate and zinc oxide. We subsequently show that these mixed ZnO-Zn 2 TiO 4 films can be successfully converted into hierarchically porous thin films of TiO 2 while retaining adhesion and with an increase in accessible surface area.…”
mentioning
confidence: 98%